“Comportamiento agronómico y rendimiento del cultivo de arroz (Oryza sativa, L), bajo diferentes niveles de fertilización órgano mineral nitrogenado, en la zona de Babahoyo”. - Vera Bacusoy, Julio Ariel (2019)
SUMMARY At present, nitrogen fertilizers are applied according to the requirement or extraction of the plant, which is detected through the analysis of the soil, without considering the efficiency of the same, this being the reason why many crops do not express their maximum potential. performance. This study measured the efficiency of BLACKGOLD mineral organ fertilization, replacing the amounts of nitrogen usually applied with Urea. The general objective was to determine the agronomic performance and yield of the rice crop (Oryza sativa, L), under different levels of nitrogen mineral organ fertilization, in the Babahoyo area. The work was developed in the CEDEGE project, of the Babahoyo county of Los Ríos province. Located at Km 12 of the Babahoyo - Montalvo road. The sowing material used was the SFL-11 variety from Pronaca. The treatments were constituted by four doses of BLACKGOLD nitrogenous organ fertilizer, and a conventional control (using urea source). The design used was Complete Random Blocks (DBCA), with five treatments and four repetitions. Only statistically significant differences were detected in the plant height and yield variables. For the plant height of treatments T1 and T2, they obtained the highest values in plant height, with 123, 88 cm for urea and 125.98 for BLACKGOLD. The treatment T5 with fertilization decreased by 75 % and using as source BLACKGOLD was the one who obtained the lowest height 120,34 cm. In the performance variable the analysis of variance detected highly significant differences between treatments and the coefficient of variation was 0,75 % and an average of 6167,20 kilograms. The T1 treatments; T2 and T3 obtained the highest amount of weight in kilograms 6272,00 kg; 6332,50 kg and 6250,25 kg respectively. The control treatment T5, had the lowest weight in kilograms 5871,25 kilograms. Keywords: fertilization; humic acids; agronomic efficiency.